Effects of Women in Top Management Teams on Corporate Wrongdoing: The Moderating Roles of Chairwoman and Female Relational Capital - Huang, Xin (Archives of Business Research, 2023)
In recent years, corporate wrongdoing has attracted widespread attention worldwide, and the media has vigorously debated whether senior management should be held accountable. Based on upper echelons theory, this study aims to investigate the relationship between women’s representation in top management teams and corporate wrongdoing, as well as the moderating roles of the presence of a chairwoman and female relational capital. This research employs data from 333 small and medium-sized enterprises listed on the Shenzhen Stock Exchange in 2017 and mainly finds through regression analysis that: in small and medium-sized enterprises in China, women’s representation in top management teams has a significant and negative impact on corporate wrongdoing; the presence of a chairwoman strengthens the negative effect, but female relational capital weakens the negative effect. This paper not only enriches research on female executives but also provides some references for companies to promote the construction of diverse top management teams.